Vector Control of Doubly Fed Induction Generator Based on Sliding Mode Variable Structure - Yaoming ZHU; Lanhong ZHANG; Lulu CHEN (南方能源建设)
[Objective] Current loop is an important control link in the grid-connection process of doubly fed induction generator (DFIG). Aiming at the poor dynamic performance of doubly fed wind power generation system during parameter uptake in traditional PI control and the buffeting problem in traditional reaching law sliding mode control, the sliding mode variable structure is studied and designed. [Method] The research method of vector control of DFIG based on sliding mode variable structure mainly focused on utilizing the advantages of sliding mode variable structure control, such as fast response speed, insensitivity to parameter changes and perturbations, etc., and combining with the characteristics of DFIG to realize accurate vector control. First, the sliding mode surface was designed to ensure that the system state slides on the sliding mode surface, and then the sliding mode controller was designed to stabilize the system state and adjustments were made to enable the system to track the desired trajectory through feedback, to achieve efficient and stable control of DFIG. Additionally, the anti-buffeting factor was combined with the power function to design the reaching law function, proposing a kind of improved power function to improve the controller's performance. A sliding mode controller based on improved power function was then constructed. [Result] Simulations show that the control process of the sliding mode controller based on an improved power function is almost free of overshooting under sudden wind speed changes. [Conclusion] Compared with the traditional PI regulator, the sliding mode controller based on an improved power function has excellent dynamic performance and control accuracy, effectively improving the control effect, stability, and anti-interference ability in the doubly fed wind power generation system.